Ocal siebie, aby ocalić świat – filozofia Małego Księcia - Czajka, Łukasz (Humaniora. Czasopismo Internetowe, 2020)
The main research task of the paper is to reconstruct The Little Prince’s philosophy. It is a philosophy of humanism created as a response to the spiritual crisis of Western culture. The mission of this philosophy is to save humans to save the world of fundamental values such as love, friendship, and responsibility. It is also the philosophy of the meeting, which enters into a dialogue with representatives of the philosophical tradition (Schopenhauer, Nietzsche, Žižek) and popular culture artists.